2003
DOI: 10.1046/j.1365-2036.2003.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome: effective and safe treatment with Phosphates Polyfusor

Abstract: Summary Background:  Severe hypophosphataemia associated with refeeding syndrome requires treatment with intravenous phosphate to prevent potentially life‐threatening complications. However, evidence for replacement regimens is limited and current regimens are complex and replace phosphate inadequately. Aim:  To assess the effectiveness and safety of 50 mmol intravenous phosphate infusion, given as a ‘Phosphates Polyfusor’, for the treatment of severe hypophosphataemia in refeeding syndrome. Methods:  Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…This required overnight i.v. intervention as mentioned earlier (6). While serum transaminases (AST and ALT) were normal at the end of the fast, elevated concentrations were detected by day 10 (Table 3).…”
Section: Resultsmentioning
confidence: 56%
“…This required overnight i.v. intervention as mentioned earlier (6). While serum transaminases (AST and ALT) were normal at the end of the fast, elevated concentrations were detected by day 10 (Table 3).…”
Section: Resultsmentioning
confidence: 56%
“…Some patients will require multiple doses over several days to completely correct hypophosphatemia, especially those with severe malnutrition/refeeding syndrome, those with P depletion, and critically ill patients. 57,61,62,65,70,74 Finally, when using weight-based dosing, there are no definitive data or recommendations for "adjusting" weight in obese patients or what threshold should be used to adjust weight (eg, using a percentage above ideal body weight [IBW] or based on body mass index). Total body water is slightly higher in males than in females, and adipose tissue is composed of approximately 10%-30% water.…”
Section: And Ca Compatibility In Pn Admixturesmentioning
confidence: 99%
“…Terlevich et al reported efficacy of 50 mmol phosphate infused into a peripheral vein over 24 hours in 30 patients with no pre-existing renal dysfunction on general wards. 17 Further infusions may be required and so careful monitoring of blood levels is required. Caution is needed in patients with existing renal impairment, hypocalcaemia (which may worsen), or hypercalcaemia (which may result in metastatic calcification).…”
Section: Body Mass Index (Kg/m 2 ) <16mentioning
confidence: 99%